P164 Use of beta-agonists prior to hospital attendance for severe exacerbations of asthma: insights from a randomised controlled trial using electronic monitoring of inhaler use. (14th November 2013) - Patel, M; Pilcher, J; Shaw, D; Weatherall, M; Knox, A; Beasley, R
Abstract : Introduction: Observational studies have reported that the overuse of inhaled beta-agonists during severe asthma is a common feature associated with a fatal outcome. However, patterns of actual use of beta-agonists prior to hospital attendance for severe exacerbations are poorly understood. Objectives: We have recently reported that in 303 adult asthma patients randomised to receive either combination budesonide/formoterol metered dose inhaler (MDI) as part of a single maintenance and reliever therapy regimen ('SMART') or as fixed-dose maintenance treatment with salbutamol MDI for relief ('Standard'), overuse of beta-agonists without subsequent medical review occurred commonly in both groups. We now report on the use of beta-agonists by patients who attended hospital with a severe exacerbation of asthma. Our hypothesis was that extremely high beta-agonist doses would be used by patients in both groups and that inhaled corticosteroid (ICS) non-adherence may occur in the Standard group during severe asthma. Methods: Data on MDI use, as measured by electronic monitoring, were extracted for each patient for the 14 24-hour periods before the attendance time at hospital for a severe exacerbation. Results: Electronic data were available for 7/7 and 9/11 hospital attendances in the SMART and Standard groups respectively. The median (range) daily number of actuations 14 days before hospital attendance was 4 (2 to 12) budesonide/formoterol in SMART and 4 (0 to 26) salbutamol and 2 (0 to 8) budesonide/formoterol in Standard. This increased to 11 (6 to 39) budesonide/formoterol in SMART and 25 (3 to 86) salbutamol and 4 (0 to 39) budesonide/formoterol in Standard, in the 24-hours before attendance. The median (range) maximum daily number of actuations was 14 (9 to 63) budesonide/formoterol in SMART and 46 (6 to 95) salbutamol in Standard. Repeated days of no ICS use occurred in 3/9 patients in the Standard group, despite concomitant salbutamol overuse. Conclusions: Very high doses of beta-agonists are commonly self-administered by patients for prolonged periods prior to hospital presentation with severe asthma. The opportunity exists for clinical review and appropriate medical intervention during this period, which may reduce the risk of a life-threatening attack.